Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Batanghari, Jambi - Marisa Marisa; Ade Rahima; Erlina Zahar (Universitas Batanghari, 2018)
This research is aimed at describing educational character values in the seloko wedding custom in Desa Niaso Kabupaten Muaro Jambi. There are 13 aspects of educational character values, they are: honesty, bravery, trusteeship, fair, wisdom, responsibility, discipline, autonomous, respectful, affection, beauty, tolerance, and love to country. This research is qualitative and is analyzed descriptively. The technique of collecting the data is by using observation, interview, and documentation. Based on the result of the analysis, it can be found that there are 8 aspects of educational character values in the seloko wedding custom in Desa Niaso Kabupaten Muaro Jambi. Those 8 aspects consist of honesty, bravery, responsibility, respectful, affection, beauty, and tolerance. Based on the result of the research, it is suggested to the region government that those educational character values in the seloko wedding custom must be maintained as one of the lessons of life in society.Key Words: Analysis, educational character values, seloko.